Nebhāraleṇḍa - Caudhurī, Rītā (The Reads Factory, 2023)
Three-part series, the novel intricately navigates the Bangladesh Liberation War.
Historical novel
Keywords: Bangladesh; History; Revolution; 1971; Fiction.; Historical fiction.; Assamese fiction.; Historical fiction.; lcgft